Nieznany dotychczas fragment rękopisu staro-cerkiewno-słowiańskiej czteroewangelii koń. XIV(?)-I poł. XV w. Prawosławnego Seminarium Duchownego w Sofii - Ostapczuk, Jerzy (Slavistica Vilnensis, 2010)
This article is devoted to an unknown folio from a churchslavonic tetragospel preserved at the Orthodox Seminary of St. John of Rila in Sofia. It contains the following descriptions: condition or the manuscript; dating; Gospel text (which was compared with critica1 edition of the Gospel of St. John) and its redaction; liturgical information; language, etc.